Developing and evaluating a paper-and-pencil test to assess components of physics teachers' pedagogical content knowledge - Kirschner, Sophie; Borowski, Andreas; Fischer, Hans E.; Gess-Newsome, Julie; von Aufschnaiter, Claudia (International journal of science education, 2016)
Teachers' professional knowledge is assumed to be a key variable for effective teaching. As teacher education has the goal to enhance professional knowledge of current and future teachers, this knowledge should be described and assessed. Nevertheless, only a limited number of studies quantitatively measures physics teachers' professional knowledge. The study reported in this paper was part of a bigger project with the broader goal of understanding teacher professional knowledge. We designed a test instrument to assess the professional knowledge of physics teachers (N = 186) in the dimensions of content knowledge (CK), pedagogical content knowledge (PCK), and pedagogical knowledge (PK). A model describing the relationships between these three dimensions of professional knowledge was created to inform the design of the tests used to measure CK, PCK, and PK. In this paper, we describe the model with particular emphasis on the PCK part, and the subsequent PCK test development and its implementation in detail. We report different approaches to evaluate the PCK test, including the description of content validity, the examination of the internal structure of professional knowledge, and the analysis of construct validity by testing teachers across different school subjects, teachers from different school types, pre-service teachers, and physicists. Our findings demonstrate that our PCK test results could distinguish physics teachers from the other groups tested. The PCK test results could not be explained by teachers' CK or PK, cognitive abilities, computational skills, or science knowledge.